2015
DOI: 10.3233/rnn-150495
|View full text |Cite
|
Sign up to set email alerts
|

Anodal transcranial direct current stimulation of motor cortex does not ameliorate spasticity in multiple sclerosis

Abstract: Five-daily sessions of anodal tDCS to the primary motor cortex does do not improve lower limb spasticity in MS patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
70
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(72 citation statements)
references
References 36 publications
0
70
0
2
Order By: Relevance
“…21 On the contrary, in a randomized study on 20 patients with spasticity, no significant clinical improvement was found after real or sham tDCS applied to the lower limb motor representation for 5 consecutive days. 22 Improvement in hand dexterity in pwMS and cerebellar symptoms after rTMS targeting M1 has been reported shortly after a single session 23 and up to 1 month after two consecutive sessions. 24 Also, 10 daily sessions of iTBS over the hand M1 were associated with significantly better improvement of manual dexterity compared with sham stimulation.…”
Section: Pyramidal Functionmentioning
confidence: 99%
“…21 On the contrary, in a randomized study on 20 patients with spasticity, no significant clinical improvement was found after real or sham tDCS applied to the lower limb motor representation for 5 consecutive days. 22 Improvement in hand dexterity in pwMS and cerebellar symptoms after rTMS targeting M1 has been reported shortly after a single session 23 and up to 1 month after two consecutive sessions. 24 Also, 10 daily sessions of iTBS over the hand M1 were associated with significantly better improvement of manual dexterity compared with sham stimulation.…”
Section: Pyramidal Functionmentioning
confidence: 99%
“…Although there are a large number of pharmacological and non-pharmacological methods of spasticity management, the problem is still challenging [3][4][5][6][7]. In this regard, the development of new methods of treatment of spasticity has great practical importance.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, reduced spasticity was associated with both changes in local connectivity and in the inter-hemispheric balance (Boutière et al, 2017 ). Conversely, one study reported that anodal tDCS on M1 for 5 consecutive days had no clinical impact on spasticity in MS patients (Iodice et al, 2015 ).…”
Section: Nibs and Symptoms Recovery In Msmentioning
confidence: 99%